Проблеми використання науково-технічних засобів і методів в ході проведення негласних слідчих (розшукових) дій - Гора, І.; Hora, I. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті проаналізовано проблеми використання сучасних науково-технічних засобів при проведенні негласних слідчих (розшукових) дій, правомірність і вимоги до порядку їх застосування для отримання стороною обвинувачення доказів. Звертається увага на їх види й особливі вимоги до таких науково-технічних засобів, залежно від мети проведення процесуальних дій, що обумовлені негласністю застосування, необхідністю дотримання конституційних прав учасників кримінального провадження. The article highlights actual problems of using scientific and technical means and methods in the course of carrying out secret investigative (search) actions. The legislator assigns directly to the investigator or to the operational units of the authorized bodies the powers to determine the type of secret investigation. They decide on the necessity to use the proper technical means, forensic techniques and methods and determine the order of operative tactical actions. The emphasis is laid on the development and implementation of scientific and technical means into the practice of pre-trial investigation, especially in carrying out secret investigative (search) actions. The author argues that appliance of them facilitates the investigation and helps to identify, detect, capture and explore various details and objects related to the criminal case. Most of the secret investigative actions require not only special knowledge and skills to perform such work, not only the use of various technical means, but also the ability to select precisely the relevant means, the use of which in some cases ought to be concealed as not to reveal the intentions of the bodies of the pre-trial investigation for some period of time.
Problems of Use of the Scientific-Technical Means and Methods in the Course of Secret Investigation (Search) Actions
Keywords: досудове розслідування; докази й доказування; науково-технічні засоби; негласні слідчі (розшукові) дії; scientific and technical methods; secret investigative actions; pre-trial investigation; scientific and technical means